Enhancing asphaltic mixtures with Calcined Nano Montmorillonite: A performance assessment - Amjad H. Albayati; Yu Wang; Aliaa F. Al-ani (Case Studies in Construction Materials, 2024)
There are increasing interest in using nanoclay particles to improve asphalt binder and the produced concrete in pavement engineering. However so far most of the study was to directly use the nanoclays in natural material conditions, which come with some inefficient factors affecting the final effectiveness of the modified asphalt binder and the made concrete. This paper reports extensive experimental research on using preprocessed nanoclay, the Calcined Nano Montmorillonite (CNMM), to modify asphalt binder, compared with using natural Nano Montmorillonite (NMM). The nanoclays were added in asphalt as additive at different content rates ranging from 0% to 10% by the weight of asphalt binder. Experimental tests were performed on both of the modified asphalt binders and the concrete mixes using them. The study showed that at a 10% content CNMM demonstrated 32% improvement on Indirect Tensile Strength (ITS), and 5.25% less permanent deformation after exposed 10,000 load repetitions; at 6% CNMM presented 57.5% improvement on the CTindex for fatigue resistance. Meanwhile, the SEM analysis proved a distinctive morphological difference between NMM and CNMM, which indicates the optimized microscopic structure of the CNMM for the improvement on the interlock and adhesion with asphalt binder. In comparison, the optimum dosage for NMM is identified at 4%, while CNMM is at around 6%. The economic viability of the use of CNMM against the use of NMM has also been discussed in reference to the local material prices. In consideration of a balance between cost and performance, 6% content is recommended for the use of CNMM.